METHODOLOGY OF DEVELOPING VALEOLOGICAL COMPETENCE IN NON-MEDICAL STUDENTS THROUGH CLOUD TECHNOLOGY - Shevchenko , A. (Problems of Engineer-Pedagogical Education, 2023)
Health-saving is an important aspect of the work of many institutions and organizations of Ukraine, regulated by the Constitution of Ukraine, a number of laws, national and regional target programs and state educational standards. The educational environment is a convenient area for the systematic study of issues of a healthy lifestyle, safe behavior, formation of the necessary skills and abilities of providing emergency aid in critical situations. The outcome of valeological education should be the formation of valeological (healthsaving) competence. The article discloses the method of forming this competence at the conceptual, technological, substantive and control-diagnostic levels. The methodology is based on the study of valeological disciplines "Fundamentals of Medical Knowledge and Health-Saving" and "Health Pedagogy" in non-medical higher education institutions for students of the "bachelor's" and "master's" educational levels. The forced distance learning in these disciplines since the start of the COVID-19 pandemic and full-scale war has made cloud technologies the main means of teaching. The article demonstrates the approaches, principles, methods and means of valeological competence formation in these conditions at a sufficient level. Didactic adaptation of medical information for teaching valeological disciplines to non-medical students takes place by simplifying it using methods of system analysis, expert evaluations, balancing, scaling and aggregation. In today's pandemic and wartime circumstances, instructing valeological subjects relies heavily on employing informationcommunication (cloud) technologies. Both educators and students need a certain proficiency level in using these technologies. Developing valeological competence among non-medical students entails teaching "Health Pedagogy." Initially led by instructors with medical and pedagogical backgrounds, there is potential for a transition to instructors solely equipped with pedagogical expertise, following a relay principle.